2003
DOI: 10.1021/bm025727p
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Strong Intermolecular Interactions in Immiscible Blends of Poly(vinyl alcohol) (PVA) and Lignin

Abstract: The intermolecular interactions of lignin with a hydrophilic polymer, poly(vinyl alcohol) (PVA), were studied using thermal analyses and FT-IR spectroscopy of a series of PVA/hardwood kraft lignin blend fibers prepared by thermal extrusion. Although two phases are observed in this blend system, some of the lignin was closely associated with the PVA in the PVA-rich phase. The crystallinity of the PVA fraction was reduced with increasing lignin content. An interaction energy density of -9.34 cal cm(-1), calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(182 citation statements)
references
References 38 publications
11
161
0
1
Order By: Relevance
“…Other researchers have detected a similar phenomenon where the polymer matrix was also reduced with increasing content of not only lignin, but also organoclay (Kubo and Kadla 2003;Gordobil et al 2014). This has been found to act as a retardant if a strong interaction exists between the polymer matrix and the organoclay (Di et al 2003;Lee et al 2008).…”
Section: Crystallization Of Pla/lignin Compositesmentioning
confidence: 64%
“…Other researchers have detected a similar phenomenon where the polymer matrix was also reduced with increasing content of not only lignin, but also organoclay (Kubo and Kadla 2003;Gordobil et al 2014). This has been found to act as a retardant if a strong interaction exists between the polymer matrix and the organoclay (Di et al 2003;Lee et al 2008).…”
Section: Crystallization Of Pla/lignin Compositesmentioning
confidence: 64%
“…For instance, the interaction between alkaline lignin (with its network structure) and long PVA chains results in great resistance to the movement of PVA chains, forming an entangled struc-ture. Besides, the formation of strong intermolecular hydrogen bonds between the hydroxyl groups of PVA and lignin also enhances the tensile strength of the membrane (Kubo and Kadla 2003). With the mass of alkaline lignin increasing, a part of alkaline lignin and PVA chains can bind tightly, but another part of alkaline lignin cannot be coupled with PVA tightly, and only act as infillings in the network structure of alkaline lignin.…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 99%
“…Thus the blends exhibit suitable interfacial binding force (Yue and Chen 2010). Kubo and Kadla (2003) have indicated that PVA is a polymer miscible with lignin, and a high degree of intermolecular interaction takes place between lignin and the PVA chains. Although both miscibility and morphology of lignin/PVA blends have been studied, the effect of alkaline lignin blending with PVA on the properties of membrane has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of hydrogen bonds was pointed out in several publications by a number of authors. They were thought to be significant in poly(vinyl chloride) [31,33], poly(vinyl alcohol) [34,35], poly(lactic acid) [37][38][39], and polyhydroxybutyrate [42,43]. In spite of the importance of hydrogens bonds, Doherty et al [54] claimed that they alone are not sufficient to compete successfully with the strong interactions among lignin molecules and to result in complete miscibility.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of papers have been published on the blends of lignin with a wide range of polymers including proteins [10][11][12], starch [13][14][15], polyolefins [16][17][18][19][20][21][22][23][24][25][26], vinyl polymers 4 [18,19,21,[27][28][29][30][31][32][33][34][35] and polyesters [19,21,22,[36][37][38][39][40][41][42][43]. The chemical modification of lignin [10,14,16,[20][21][22]27,29,36,40,…”
Section: Introductionmentioning
confidence: 99%